Восстановление бетона и железобетона проникающей гидроизоляцией - Кондращенко, Е. В.; Костюк, Т. А. (НТУ "ХПИ", 2008)
Розглянуто принцип перетворення структури цементного каменя в бетоні продуктами синтезу хімічно активної частини гідроізоляції проникної дії і порового електроліту цементного каменя.

There is considered the cement stone structure transformation on the concrete via products of synthesis of the chemically active part of penetrative damp course and steam electrolyte of the cement stone.
Keywords: поровый электролит; коррозия; вяжущие вещества; реакция гидратации; структурообразование